Evaluating good practice in coaching delivery between governing bodies of sport and county sports partnerships in the United Kingdom. Issue 1 (2nd January 2016) - Baker, Colin; Vinson, Don; Parker, Andrew
ABSTRACT: Forty-nine county sports partnerships (CSPs) work together with national governing bodies of sport (NGBs) to support and develop sports coaching in the United Kingdom. Partnership has been promoted as a key means by which agencies are able to address complex issues, but to date there has been little, if any, research into the effectiveness of partnership working between NGBs and CSPs in their support of coaching delivery. NGB officers ( n  = 13) and CSP Coaching Development Managers (or equivalent) ( n  = 23) were asked (via online questionnaire and telephone interviews) about their experiences of partnership working. Findings demonstrate that successful partnership working relies heavily upon 'buy-in' from both parties and an adequate amount of funding to support coach development. The paper concludes by suggesting that it is likely that partner agencies may need to be persuaded about the value of partnership working due to the required investment and the perceived burdens of collaboration.